Servicios de saneamiento básico asociado a calidad de vida de los pobladores del Asentamiento Humano Jorge Monasí Iquitos 2023 - Ampudia Navarro, Jonás (2025)
The purpose of the study was to establish an association between basic sanitation services and quality of life of the inhabitants of the Jorge Monasí Nursing Home. The quantitative, descriptive, observational, cross-sectional and correlational approach; The sample consisted of 150 inhabitants. The survey, and instruments a Questionnaire of basic sanitation services (validity 82.0%, reliability 81.2%) and quality of life scale (standardized). The results obtained were: basic sanitation services were moderately adequate 53.3%, inadequate 24.7% and adequate 22.0%; healthy quality of life 55.3% and unhealthy 44.7%; 68.7% and 70.0% predominating as healthy in physical and psychological health; in quality of life and health 88.7%, social relationships 86.0% and environment 86.7% as unhealthy. When relating both variables, through Spearman, statistical significance was found (p = 0.000 < α = 0.05); in water supply service (use and consumption) (p = 0.000), sanitary availability of excreta (p = 0.000) with quality of life; while with sanitary garbage management (p = 0.773) there was no significance. Concluding that the inhabitants tend to perceive the level of basic sanitation services as moderately adequate, leading them to value healthy quality of life.